Euro area inflation-linked bonds market: analysis and immunization abilities - Simões, Cláudia Patrícia Gonçalves (2017)
This thesis focuses on inflation-linked bonds. These bonds, although not as popular as other types of bonds, are not a new instrument. The first inflation-linked bond issue took place in the United States in the eighteenth century. In Europe, it would be only in the end of the twentieth century that inflation-linked bonds would be issued in a regular basis by European Monetary Union participant countries. This thesis objective is twofold: to characterize this type of bonds and evaluate their immunization abilities. The first part of this study focuses in defining and describing thoroughly these bonds: their issuers, security design, indexation choice and applications. The second part is dedicated to investigating which portfolio strategies using inflation-linked bonds achieve better immunization results for single inflation-growing liabilities. Simulations were made for investment horizons between one and five years, with and without transaction costs. The results presented point to the superiority of bullet portfolios, over random and barbell portfolios, in terms of liability coverage. Bullet portfolios also prove to be less volatile. These aforementioned results hold in the presence of transaction costs. It is also visible that the portfolios’ return is very sensitive to the evolution of the real term structure of interest rates. As for the comparison between fixed rate bonds and inflation-linked bonds, the latter prove to be better suited to immunize the liabilities under analysis.